Chromosomal Aberrations in Turkish Infertile Couples with Reproductive Problems - Osman Demirhan; Nilgün Tanrıverdi; Dilara Süleymanova (Global Journal of Fertility and Research - Peertechz Publications, 2016)
Aim of the study: Infertility is a relatively common health condition, affecting nearly 15% of all couples, and has been estimated that nearly 50% of infertility cases are due to genetic defects. Chromosomal aberrations (CAs) contribute to infertility and repeated miscarriage leading to reproductive failure in couples. Objective: To determine the frequency and types of CAs in unexplained infertile couples with reproductive problems, and the association between clinical background and genetic abnormality. Materials and method: This study was a retrospective analysis to examine the CAs and prevalence in 160 couples and 210 individuals with unexplained infertile problems, and 58 control cases. The samples were cultured routinely for the karyotype analysis using G banding. Results: CAs were detected in 9.8% of total 530 infertile individuals, and in 12% of all 160 couples (320 individuals). In the control group, CAs were only found in 3.4% of 58 healthy volunteers. The 50.0% of these CAs was structural aberrations, and also numerical CAs was 50.0% in infertile individuals. Specifically, 47, XXY (Klinefelter syndrome-KS) karyotype was the most common. Aneuploidies were present in 1.1% of infertile individuals. Among numerical CAs; mosaic Turner, X chromosome mosaic and interseks were detected only in one case for each numerical CA type. Reciprocal translocations were present in 0.8% of infertile individuals. The inversions and the other variants were present in 1.9% and 2.3% of infertile individuals, respectively. The incidence of abnormal karyotypes was higher in males than females. Conclusion: The results suggest that CAs were a major cause of infertility in humans, and cytogenetic analysis should be strongly recommended for infertile individuals. The incidence of CAs in infertile men was 3-fold greater than reported in infertile women. These findings will could be used widely in the clinical genetics and will be an effective tool for genetic counseling and reproductive guidance.